Development of priority oriented scheduling method to increase the efficiency and reliability for automotive job - Nojabaei, Seyedehfarzaneh (2012)
Scheduling occurs in every organization without considering the nature of its activities. In this regard, numerous scholars have attempted to schedule via divergent methods including classical scheduling, genetic algorithm, neural network, fuzzy logic, and so on. Studies in manufacturing scheduling mostly deal with priority rules without considering the system states. An appropriate scheduling leads to significant enhancement of fairness in job scheduling. The term fairness can be transformed into a specific selection of job weights. There is no method of scheduling in which “Priority, Time Action (duration), and Time Stamp” of jobs have simultaneously been considered. The proposed method of scheduling can enhance the efficiency and reliability of manufacturing systems via considering aforementioned aspects. To fulfill this target, first and foremost, the normalize method should be performed. This method allows data (time stamp, time action,priority) of jobs on different scales to be compared by bringing those to a common scale. Secondly, the jobs should be arranged based on three criteria which are priority, time action and time stamp. This sorting algorithm is programmed via MATLAB distributed computing server (DCS) software. Eventually, to evaluate the proposed method of scheduling, simulation is operated. The simulated algorithm shows that applying the proposed method of scheduling increases the efficiency of simulated scheduler in comparison with common method of scheduling. Besides the mentioned simulated algorithm, there is a mathematical proof to prove the enhancement of reliability. Also, to evaluate the proposed method of scheduling, a case study in an automotive manufacturing company (IKCO) is conducted. In this case study, cause and effect analysis was employed. Therefore, the causes derived from ignoring priority and time action are determined. By applying the proposed method of scheduling, the mentioned causes are spontaneously eliminated. To show the significant difference between efficiency of system before and after applying proposed method of scheduling pair sample t-test is employed. Also, this test is operated to show the significant difference between reliability of system after and before employing the proposed method of scheduling. Finally, the provided results (Sig. (2-tailed) = 0) show that there are remarkable enhancement in efficiency and reliability of system by applying the proposed method of scheduling.